The Effect of Zinc-Proteinate Supplementation on the In Vitro Digestibility and Ruminal Fermentation in Goat - Nathaniel, Gilbert; Annisa, Tiara; Muktiani, Anis; Harjanti, Dian Wahyu; Widiyanto, Widiyanto (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2021)
This study aimed primarily to investigate the effect of Zn-Proteinate (Zn-Prot) supplementation on in vitro rumen digestibility and rumen fermentation. This research used a completely randomized design with four treatments and four replicates. The experimental treatment was the supplementation of various levels of Zn-Prot (0; 12.5 ppm; 25 ppm, and 37.5 ppm) on a dry matter basis. Parameters determined were in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), partial volatile fatty acid (VFA) (acetate, propionate, and butyrate), A/P ratio, CH4, and the efficiency of the conversion hexose to VFA. Data were analyzed using ANOVA. The results showed that goats fed with a diet supplemented with 25 ppm Zn-Prot had the highest IVDMD and IVOMD values. There was no significant effect on the VFA and CH4 concentrations, A/P ratio, and the efficiency of the hexose-VFA conversion within treatment groups. In conclusion, supplementing 25 ppm of Zn-Prot into the diet of dairy goat increase the dry matter and organic matter digestibility.